Impact of L-ornithine L-aspartate on non-alcoholic steatohepatitis-associated hyperammonemia and muscle alterations - Pichon, Camille; Nachit, Maxime; Gillard, Justine; Vande Velde, Greetje; Lanthier, Nicolas; Leclercq, Isabelle A. (Frontiers in Nutrition, 2022)
Background Metabolic dysfunction-associated fatty liver disease (MAFLD) is the most common chronic liver disease in the world. Progression towards non-alcoholic steatohepatitis (NASH) is associated with alterations of skeletal muscle. One plausible mechanism for altered muscle compartment in liver disease is changes in ammonia metabolism. In the present study, we explored the hypothesis that NASH-associated hyperammonemia drives muscle changes as well as liver disease progression. Methods In Alms1-mutant mice (foz/foz) fed a 60% fat diet (HFD) for 12 weeks, we investigated hepatic and muscular ammonia detoxification efficiency. We then tested the effect of an 8 week-long supplementation with L-ornithine L-aspartate (LOLA), a known ammonia-lowering treatment, given after either 4 or 12 weeks of HFD for a preventive or a curative intervention, respectively. We monitored body composition, liver and muscle state by micro computed tomography (micro-CT) as well as muscle strength by four-limbs grip test. Results According to previous studies, 12 weeks of HFD induced NASH in all foz/foz mice. Increase of hepatic ammonia production and alterations of urea cycle efficiency were observed, leading to hyperammonemia. Concomitantly mice developed marked myosteatosis. First signs of myopenia occurred after 20 weeks of diet. Early LOLA treatment given during NASH development, but not its administration in a curative regimen, efficiently prevented myosteatosis and muscle quality, but barely impacted liver disease or, surprisingly, ammonia detoxification. Conclusions Our study confirms the perturbation of hepatic ammonia detoxification pathways in NASH. Results from the interventional experiments suggest a direct beneficial impact of LOLA on skeletal muscle during NASH development, though it does not improve ammonia metabolism or liver disease.